The Lomborg deception : setting the record straight about global warming - Friel, Howard, 1955- (Yale University Press, 2010)
Friel's book is the first to respond directly to Lomborg's controversial research as published in The Skeptical Environmentalist (2001) and Cool It: The Skeptical Environmentalist's Guide to Global Warming (2007). His close reading of Lomborg's textual claims and supporting documentation reveals a lengthy list of findings that will rock climate skeptics and their allies in the government and news media, demonstrating that the published peer-reviewed climate science, as assessed mainly by the UN's Intergovernmental Panel on Climate Change, has had it mostly right--even if somewhat conservatively right--all along. Friel's able defense of Al Gore's An Inconvenient Truth against Lomborg's repeated attacks is by itself worth an attentive reading. --Publisher's description.